(3GdQjGVjGJ aj(B( (3GdLHQ(B) /s - (3YjSi, GSeGA YHO GdcQjes ((3YeGf(B: s (3OGQ UaGA(B, s, 2008)
(3JVef gPG GdcJGH eGjdj (B: (3ebOeI (B: (3GdeLehYGJ (B: (3WQb cJGHI GdeLehYGJ (B: (3CfhY GdeLehYGJ (B: (3JeKjd GdeLehYGJ (B: (3GdYedjGJ GdJj JJe Ydi GdeLehYGJ (B: (3GJMGO eLehYJjf (B: (3JbGWY eLehYJjf (B: (3GdeLehYI GdcGedI (B((3GdeJeeI(B) : (3aQb Hjf eLehYJjf (B: (3GdeLehYGJ GdefaUdI (B: (3YOO YfGUQ GdeLehYI (B: (3VQH eLehYJjf (B: (3JeKd GdVQH GdcGQJjRj HjGfjG (B: (3GdCYOGO GdMbjbjI (B: (3GdCYOGO ZjQ GdfSHjI (B: (3GdYdGbI Hjf M, c hGdCYOGO ZjQ GdfSHjI (B: (3HYV NhGU GdCYOGO GdMbjbjI (B: (3GdbGSe GdeTJQc GdCcHQ hGdeVGYa GdeTJQc GdCUZQ (B: (3JMdjd GdcShQ GdYGOjI Edi cShQ YTQjI (B: (3JMhjd GdcThQ GdYTQjI Edi cShQ YGOjI (B: (3GdeLGd (B((3GdaJQGJ(B) : (3GdJMdjd (B: (3GdeYGOdGJ (B: (3GdeYGOdGJ GdNWjI (B: (3GdeYGOdGJ GdNWjI (B: (3GdeYGOdGJ GdNWjI aj KdGK eLGgjd (B: (3eYGOdGJ GdOQLI GdKGfjI aj eLghd hGMO (B: (3Md fXGe echf ef eYGOdI NWjI heYGOdI JQHjYjI (B: (3Md eYGOdGJ ef GdOQLI GdKGdKI HeJZjQ hGMO (B: (3GdCSS (B: (3GdeJHGjfGJ (B: (3GdNhGU GdgGeI ddeJHGjfGJ (B: (3GdbjeI GdeWdbI (B: (3NhGU GdbjeI GdeWdbI (B: (3GSJNOGe GdbjeI GdeWdbI aj Md GdeYGOdGJ (B: (3GdMd GdgfOSj (B: (3GdMd GdLHQjs
(3HjHdjhZQGajG U(B.79s
Keywords: (3GdGYOGO GdMbjbjIs; (3GdLHQs; (3GdeLehYGJs; (3GdeYGOdGJs; (3QjGVjGJs